Seen and unseen: using video data in ethnographic fieldwork. (9th November 2015) - Hackett, Abigail; Pool, Steve; Rowsell, Jennifer; Aghajan, Barsin
Abstract : Purpose: – The purpose of this paper is to report on video making in two different contexts within the Community Arts Zone research project, an international research project concerned with the connections between arts, literacy and the community. Design/methodology/approach: – At one project site, researchers and parents from the community filmed their children making dens with an artist. At another site, a professional film crew filmed young people engaged in arts practice in school settings. Findings: – In both cases, researchers, artists and community participants collaborated to do research and make video. This paper discusses the ways that this work was differently positioned at the two sites. These different positionings had implications for the meaning ascribed to video making from the point of view of the participants, researchers and artists involved. Originality/value: – By drawing on perspectives of researchers and artists, the paper explores implications for video making processes within ethnographic research. These include a need for awareness of the diversity and fragmentation of the fields of both visual research and visual arts practice. In addition, the relationship between research and the visual is unfolding in a context in which the digital is increasingly ubiquitous in everyday life. Therefore the authors argue for the need for researchers and artists to explore their epistemological assumptions with regards to video and film, and to consider the role of the digital in the lives of their participants. The coming together of these positions and experiences is what constructs the meaning of the digital and visual in the field.